KOMPOSISI JENIS-JENIS PAKAN LEBAH MADU HUTAN (Apis dorsata)DI KAWASAN HUTAN LINDUNG DESA PANJOKA KECAMATAN PAMONA UTARA KABUPATEN POSO SULAWESI TENGAH - Metungku, Arlan; Labiro, Elhayat; Rahmawati, Rahmawati (Universitas Tadulako, 2019)
Forests are one of the natural resources that have benefited human life in the form of wood or non-wood. One of the non-timber forest products is forest honey bee which is currently diminishing due to the destruction of forest honey bee habitat, some honey producers. Depending on honeybee habitat, it can affect the presence of feed because this research aims to find out the composition of feed types Forest honey bees in the protected forest area of Panjoka Village, Poso Regency. The method used in this study uses a striped path. The method used in this study uses a striped path. The area of the research object is 16 Ha. Sampling intensity 6.25%. The total number of observation plots is 25 plots, the number of lanes is 5 lanes, the distance between lanes is 50 m and the distance between plots is 50 m. Composition The overall vegetation type for tree, pole, sapling and seedling consists of 24 species and 19 families in 50 observation plots . The types of forest honey bee feed are Kasa (Castanopsis accuminatisima), Ipoli (Litocarpus hafilandii), Mbosisi (Trema cannabina Lour), Sisio (Chionanthus sordidus Kiew), Pangkula (Adinandra celebica Koord), Wayatu Yopo (Unidentified), Pakanangi (Litsea densiflora (Teschner) Kosterm), Peta'a (Pternandra coerulescen Jack), Nggalumele (Freycenetia celebica Solm), Nunu (Ficus sp), Kondongio (Cryptocarya palawanensis Merr), Wilonti (Homalanthus populneus (Geiseler) Pax), Lepati Mbawu (Bridelia glauca Blume), Sumpiti (Saularia sp), Antoli (Toonaa cyliat), Pa'u (Macadamia hildebrandii), Tea (Artocarpus elasticus Miq), Waka (Ficus elmeri Merr), Perenjongi (Horsfieldia costulata (Miq) Warb), Kasimpo ( Alpinia galangal L), Beta'u (Colophyllum soulantri Miq), Peroka (Elaeocarpus anggustifolius Blume), Uwe (Syzigium sp) and Gopu (Elaeocarpus sp).Keywords: Composition of types of forest honey bee feed